Do Chief Executives' Traits Affect the Financial Performance of Risk‐trading Firms? Evidence from the UK Insurance Industry. (28th March 2017) - Adams, Mike; Jiang, Wei
Abstract : We examine the effects of four key dimensions of Chief Executive Officers' (CEOs') traits on six financial performance metrics using panel data for 1999−2012 drawn from the UK's property−casualty insurance industry. We find that CEO insurance experience and CEO financial expertise enhance financial performance, while two other CEO traits − power and age − are generally not significant. Our results thus reinforce the importance of CEO insurance industry expertise and CEO financial expertise in the management and trading of risks. Our results have potential commercial and policy implications.